Constructing a reading comprehension test for general education ESL courses lessons learned, insights gained (2010)
This paper describes how a reading comprehension diagnostic test for ESL GE courses was constructed, validated, and used to gauge the reading skills of college students. The test includes both expository and narrative texts and likewise addresses all five levels of reading comprehension: little comprehension, interpretation, evaluation, integration, and creative reading.
The paper also enumerates, describes, and evaluates the challenges met, the problems encountered, the lessons learned, and the insights gained as the test was constructed and evaluated-all in the context of a bilingual education program in the Philippines.
Keywords: General education -- Evaluation; Reading comprehension -- Evaluation; Reading comprehension -- Ability testing